2004
DOI: 10.1097/00002371-200401000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Prostate Tumor Microenvironment Alters Immune Cells and Prevents Long-Term Survival in an Orthotopic Mouse Model Following flt3-Ligand/CD40-Ligand Immunotherapy

Abstract: A novel orthotopic metastatic model of mouse prostate cancer was developed using MHC-negative TRAMP-C1P3 (transgenic adenocarcinoma of mouse prostate) cells derived by serial passage of the parental TRAMP-C1 line in mouse prostate glands. TRAMP-C1P3 cells grew efficiently in mouse prostate glands and reproducibly metastasized to draining lymph nodes. Using this model, we show that Fms-like tyrosine kinase-3 ligand (flt3-L) dramatically inhibited growth of preexisting orthotopic TRAMP-C1P3 tumors and the develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 37 publications
1
12
1
Order By: Relevance
“…Previous studies by Troy et al (9) indicated that minimally activated tumor-infiltrating dendritic cells infiltrate the tumor mass of prostate cancer patients. In contrast, our studies and those of Ciavarra et al (27,28) suggest that the tumorinfiltrating dendritic cells have an immature phenotype. These conflicting observations may be due to analysis at different stages of tumor progression in the prostate cancer patients versus the mouse models.…”
Section: Discussioncontrasting
confidence: 91%
“…Previous studies by Troy et al (9) indicated that minimally activated tumor-infiltrating dendritic cells infiltrate the tumor mass of prostate cancer patients. In contrast, our studies and those of Ciavarra et al (27,28) suggest that the tumorinfiltrating dendritic cells have an immature phenotype. These conflicting observations may be due to analysis at different stages of tumor progression in the prostate cancer patients versus the mouse models.…”
Section: Discussioncontrasting
confidence: 91%
“…Other strategies to induce tumor immunity have also failed to mediate complete tumor rejection and have only delayed tumor growth (41,42). Recently, it was shown that orthotopically implanted TRAMPC-1P3 tumors developed an immunosuppressive microenvironment where dendritic cells failed to express costimulatory molecules and class II antigens, interfering with adequate T-cell activation (43). Given that TRAMPC-1 and TRAMPC-2 cell lines were derived from the prostate tumor of a male TRAMP mouse (44) and that the tumor growth kinetics follow the same pattern, it is possible that mSTEAP treatment at day 31 was too late to modify the tumor microenvironment, resulting in unsuccessful treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, Troy et al indicate that minimally activated DC infiltrate the tumor mass of RCC and prostate cancer patients [139,140]. Other studies suggest that the tumor-infiltration DC have an immature phenotype and could induce a partial state of Tcell tolerance to the tumor cells, suggesting that alterations in DC maturation in the tumor microenvironment may prevent them from activating antigen-specific T cells [141,142]. It is well known that if antigen-presenting cells do not express costimulatory molecules CD80 or CD86, and thereby fail to provide an appropriate second signal for T cells, tolerance pr anergy may develop [143,144].…”
Section: Regulation Of Tadc Maturation and Function At The Tumor Sitementioning
confidence: 99%